The photographers' gaze: the Mobile Radioisotope Exhibition in Latin America (1960–1965). Issue 1 (2nd January 2023) - Mateos, Gisela; Suárez-Díaz, Edna
ABSTRACT: During the IAEA's Mobile Radioisotope Exhibition (1960–1965) through the eventful roads of five Latin American countries (Mexico, Uruguay, Argentina, Brazil, and Bolivia), a variety of photographs were taken by an unknown Mexican official photographer, and by Josef Obermayer, a staff driver from Vienna. The exhibition carried not only bits of nuclear sciences and technologies, but also the political symbolism of the 'friendly atom' as a token of modernization. The photographs embarked on different trajectories, though all of them ended up at the training and exchange official's desk in charge of the exhibition, Argentinian physicist Arturo Cairo. The ones taken in Mexico also had a local circulation as propaganda intended to promote radioisotope applications. The two sets of images were intended to show the contrast between modernity and traditional society, but they did it from different gazes. Our paper argues that, in the case of Mexico, the photographer reinforced representations of the country which were already popularized by Hollywood for foreign and local audiences. On the other hand, the Viennese photographer's gaze delivers an autoethnography of his dutiful journey. We also argue that Obermayer's projection is one of what Roger Bartra has conceptualized as the 'salvage on the mirror'.